The Face of Chronic Migraine Which Has Started to be Clarified - AYDIN ÖZEMİR, Zeynep (Noro Psikiyatr Ars, 2013)
Recently, information about migraine which is generally characterized with attacks has gradually increased. In some patients with migraine, progression may be observed such that the frequency and time of the attacks are increased and an attack lasts for days. This condition is called chronic migraine (CM). According to the last classification, chronic migraine is defined as headache which occurs 15 days a month or more frequently at least 8 of which show the characteristic properties of migraine or response to migraine-specific treatment. The diagnostic cirteria of chronic migraine, its differences from other chronic daily headaches and the question if it is a migraine form with a high frequency which transforms from episodic migraine or a completely different pathophysiological picture are still contradictory. Clarifying these issues is possible with clinical studies as well as increasing the studies directed to investigate the pathophysiological mechanisms.